Visualização 3D de uma imagem digital: metodologia e potencial cartográfîco - Ros, Giovana Angelica [UNESP]; Dal Poz, Aluir Porfírio [UNESP]; Hasegawa, Júlio Kiyoshi [UNESP] (Universidade Federal do Rio Grande do Sul, 2002)
This article presents a methodology for 3D visualization of a digital image and discusses its cartographic potential. Assuming that a regular DTM (Digital Terrain Model) is available, whose points are connected to form a triangular mesh, a shading methodology is applied triangle-by-triangle. This requires the computation of gray levels of image points corresponding to the pixels of 3D visualization plane, what in turn requires the modeling of the sensor used to acquire the image. Next, a shading model may be used to add artificially an extra effect of shading to the gray levels previously obtained, generating, e.g., shadows along the most elevated slopes opposed to the artificial light source. Finally, a projection model is used to obtain the 3D perception on the visualization plane. Results obtained were sufficient, showing that the 3D visualization methodology has the potential to be used in several cartographic application, as, e.g., in the cartographic revision.
3D Visualization of a digital image: Methodology and cartographic potential
Keywords: Flat shading; Gouraud shading; Three-Dimensional viewing